Design and screening of syringic acid analogues as BAX activators-An in silico approach to discover "BH3 mimetics". (June 2018) - Cheemanapalli, Srinivasulu; C.M., Anuradha; Pakala, Suresh Babu; Chitta, Suresh Kumar
Graphical abstract: Highlights: In silico screened out syringic acid analogues possesses good Druglike property. Syringic acid analogues have shown best docking energies compared to reference compounds (BH3 mimetics). Syringic acid analogs and known BH3 mimetics interacts potently and specifically with the BAX trigger site. Point mutation described the importance of Lys21 at BAX trigger site. Abstract: Although BAX, which is a molecular hit squad that incentive apoptosis was found to be an attractive emerging target for anticancer agents. The molecular mechanism of small molecules/peptides involved in the BAX activation was remain unknown. The present focus of the study is to identification and development of novel molecules which are precisely activates BAX mediated apoptosis. In this process we identified some syringic acid analogues associated with the BAX hydrophobic groove by a virtual-screen approach. Results from the docking studies revealed that, SA1, SA9, SA10, SA14 and SA21 analogues have shown good interaction with BAX trigger site, of which SA10 and SA14 bound specifically with Lys21 at α1 helix of BAX, a critical residue involved in BAX activation. All docking calculations of SA analogues were compared with clinically tested BH3 mimetics. In this entire in silico study, SA analogous have performed an ideal binding interactions with BAX compared to BH3 mimetics. Further, in silico point mutation of BAX-Lys21 to Glu21 resulted in structural change in BAX and showed reduced binding energy and hydrogen bond interactions of the selected ligands. Based on these findings, we propose that virtual screening and mutation analysis of BAX is found to be the critical advance method towards the discovery of novel anticancer therapeutics.